2022
DOI: 10.12681/healthresj.28367
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Management of Intensive Care Unit, correlation of team climate with job satisfaction of the nurses in the ICU

Abstract: Introduction: The correlation between team climate and job satisfaction has been studied by researchers worldwide, but only a handful of them have dealt with the reality of Intensive Care Units (ICU). Team climate can contribute to nurses’ job satisfaction, thus increasing their efficiency and effectiveness. Especially during a pandemic, such as Covid-19, the investigation of team climate and job satisfaction is of great importance.Purpose: The purpose of this study was to investigate the correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
4
Order By: Relevance
“…At the international level, a study conducted in intensive care units of a public hospital in Greece, with the participation of nurses, showed that the factors "support for new ideas", "team goals" and "task orientation" were influenced by aspects of job satisfaction, such as the relationship with the supervisor/manager, the nature of the work and communication (14) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the international level, a study conducted in intensive care units of a public hospital in Greece, with the participation of nurses, showed that the factors "support for new ideas", "team goals" and "task orientation" were influenced by aspects of job satisfaction, such as the relationship with the supervisor/manager, the nature of the work and communication (14) .…”
Section: Discussionmentioning
confidence: 99%
“…The national and international literature shows a close relationship between team climate and job satisfaction, with the former being a relevant predictor of the latter in primary care settings (13) and hospital (14) . However, there is a lack of knowledge about teamwork, measured by the constructs "team climate" and "job satisfaction", as well as their relationship with sociodemographic and work characteristics, from the perspective of workers and teams in the MPHC/MECS.…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura nacional e internacional, se evidencia una estrecha relación entre clima de equipo y satisfacción laboral, siendo el primero un relevante predictor del segundo en los ámbitos de la atención primaria (13) y hospitalaria (14) . Sin embargo, se constata carencia de conocimiento sobre trabajo en equipo, medido a través de los constructos 'clima de equipo' y 'satisfacción laboral', así como sus relaciones frente a las características sociodemográficas y laborales, desde la perspectiva de trabajadores y equipos en el APHM/SAMU.…”
Section: Introductionunclassified
“…"objetivos del equipo" y "orientación hacia las tareas" fueron influenciados por aspectos de satisfacción laboral, como la relación con el supervisor/gerente, la naturaleza del trabajo y la comunicación(14) .De este modo, se corrobora que el trabajo en equipo tiene potencial y puede mejorar la satisfacción laboral por parte de los profesionales/trabajadores y, consecuentemente, propiciar mejores resultados en la atención a la salud de usuarios, familia y comunidad(9) . En relación al análisis de la asociación entre "clima en equipo" y "satisfacción laboral", moderada por las características sociodemográficas y laborales, se encontró que, en los hombres, el aumento en el puntaje del factor "apoyo para ideas nuevas" resultó en mayor satisfacción, en relación a las relaciones jerárquicas; en el género masculino, predominó la categoría de los conductores socorristas.…”
unclassified
“…Isso pode ser modificado em função de condições intrínsecas e extrínsecas, tanto do trabalho quanto do profissional (12) . Na literatura nacional e internacional, evidencia-se a estreita relação entre clima de equipe e satisfação no trabalho, sendo o primeiro um relevante preditor do segundo nos âmbitos da atenção primária (13) e hospitalar (14) . Todavia, constata-se carência de conhecimento sobre trabalho em equipe, mensurado por meio dos construtos "clima de equipe" e "satisfação no trabalho", bem como suas relações frente às características sociodemográficas e laborais, na perspectiva de trabalhadores e equipes no APHM/SAMU.…”
unclassified